THE COMPETITION MYTH: EXPLORING THE SYMBIOSIS BETWEEN HUMAN AND ARTIFICIAL INTELLIGENCE - Sarfaraz, Ambreen (Journal of Arts & Social Sciences, 2024)
The generally conceived belief that jobs are at danger of being replaced by AI has sparked concern which has resulted in human intelligence being seen as in conflict with AI systems. However, this perceived rivalry obscures a more profound reality: the integration between human beings and artificial intelligence. For that reason, this study refutes the competition myth and shows that people and AI can work together. Human intelligence is superior in adaptability, feelings and the ability to consider the circumstances, whereas AI is faster, flexible at scale, and analytical. Combinatorial of these capacities gives rise to hybrid intelligence, which essentially extends human capabilities and reconstructs problem-solving approaches. As demonstrated in this study, AI can serve to enhance human capabilities that are more valuable, work on the tasks that are best executed by human intelligence, and can create path to a new paradigm of human-AI collaboration.